1987
DOI: 10.1161/01.hyp.9.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Is beta 1-antagonism essential for the antihypertensive action of beta-blockers?

Abstract: Both nonselective beta-blockers and beta 1-selective blockers are effective antihypertensive agents. beta 1-Blockade generally is considered to be responsible for their antihypertensive action, whereas beta 2-blockade is regarded as undesirable. These common assumptions notwithstanding, the mechanism by which beta-blockers lower blood pressure remains unknown. To examine the possibility that beta 2-blockade may contribute to the antihypertensive action of beta-blocker therapy, we studied the cardiovascular eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…In accordance with our data, 2 different studies in humans also reported that ICI did not affect systemic blood pressure. 23,24 Only Vincent et al 25 found a reduction of systemic blood pressure, however, only 1 week after the beginning of treatment and when using a much higher concentration (0.7 mg/kg for patients of 70-kg weight) compared with our study. Thus, low concentrations of ICI specifically reduce vascular tone in pulmonary vessels.…”
Section: Discussioncontrasting
confidence: 67%
“…In accordance with our data, 2 different studies in humans also reported that ICI did not affect systemic blood pressure. 23,24 Only Vincent et al 25 found a reduction of systemic blood pressure, however, only 1 week after the beginning of treatment and when using a much higher concentration (0.7 mg/kg for patients of 70-kg weight) compared with our study. Thus, low concentrations of ICI specifically reduce vascular tone in pulmonary vessels.…”
Section: Discussioncontrasting
confidence: 67%
“…Procaterol treatment increased heart rate by [10][11][12][13][14][15] beats/min after 12-24 hours. During further treatment, heart rate declined slowly and reached predrug levels about 2-3 days after withdrawal of procaterol.…”
mentioning
confidence: 98%
“…In the study by Dahlof et al [24], ICI 118551 reduced heart rate and cardiac output significantly but did not alter mean blood pressure. In a more recent study by Vincent et al [26], ICI 118551, 50 mg three times daily, was compared with propranolol 80 mg three times daily and placebo in 19 hypertensive subjects. Systolic and diastolic blood pressures were significantly reduced after 7 days treatment.…”
Section: Relative Beta2 Selectivitymentioning
confidence: 99%
“…ICI 118551 causes a significant reduction in heart rate in all the studies and a fall in cardiac output in the single study where this was measured indirectly. In the negative study [26], a placebo was not used, though the subjects were known responders to other beta blockers. Thus the question as to whether selective beta 2 blockade reduces blood pressure remains controversial.…”
Section: Relative Beta2 Selectivitymentioning
confidence: 99%